MORALS, MEMORY AND COGNITION - CHAN, ADRIANO (Revista Sinergia, 2019)
Human communication must be understood as a complex mosaic. Its constitution supposes the existence of many tribes causing the rising of multiple voices Each tribe cultivates its own moral values and its own system of beliefs and cultural themes. However, we live in a globalized world and this plurality of identities can cause a lot of misunderstandings when ciphered signs of a certain subculture are appropriated. In this article we intend to describe and to analyze a theatrical experience that exploited some of these signs extracted from the gay culture. Such symbols were adapted for general audiences causing a series of critics by some activists. Key words: Codes, cognition, communication, theater, genre, gay, culture, subculture, urban tribes.